Conceptions of the Vernacular Settlement Architecture Orientation: A Literature Study of Research Results - I Kadek Merta Wijaya; Ngakan Ketut Acwin Dwijendra (International Journal of Engineering and Emerging Technology, 2021)
Architectural researchers have conducted researches on the architectural orientation of vernacular settlements, both explicitly and implicitly. The study results differ based on the understanding of the resident's culture of the community, their beliefs, and the context of their settlements. They understand that vernacular settlement architectural orientation results in a different orientation direction in one territory from another in Indonesia. Indonesia is an archipelago country with various tribes spread throughout the Indonesian archipelago. Each ethnic group has a different culture of living, so that the orientation of the Settlement as a form of relationship between tribal people and their "priority" is also different. The complexity of vernacular payments in Indonesia is fascinating to trace the grand conception through inductive studies. This study aimed to examine the conceptual orientation of the elaborate architectural direction of vernacular settlements in Indonesia using the literature method through the hermeneutic approach. The object of the study is the publication of research results in the form of journals and proceedings. The research results are (1) the conception of symbolic analogy, which means expressing an identity of immanent and transcendental relationships between people in a vernacular architectural territory with their "priority"; and (2) logical conception, understanding the existence of a place of residence as a necessity of life.